Key Factors Behind Contraceptive Use in Indonesian Women of Reproductive Age: Findings from the 2023 Health Survey - Ayu Aminatussyadiah; Amrina Nur Rohmah; Suci Fitriana Pramudya Wardani (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2026)
Background: Population control through family planning (KB) programs is crucial for improving the community's quality of life and promoting women's reproductive health. Studies on contraceptive use in Indonesia indicate that short-term methods, particularly injectables, are the most commonly chosen by users. This preference is influenced by various factors such as age, education level, employment status, and place of residence. Therefore, this study aims to analyze the factors associated with contraceptive use among women of reproductive age in Indonesia.Method: This study employed a quantitative descriptive method with a cross-sectional design to analyze data from the 2023 Indonesian Health Survey (SKI), focusing on the reproductive health component. The sample consisted of 70,649 women of reproductive age. Data analysis was performed using bivariate analysis, specifically the Chi-square test, to examine the relationship between independent variables and contraceptive use. Statistical analysis was conducted using SPSS version 26.0, with a significance level of p < 0.05 considered statistically significant.Results: The results of this study indicate that all variables influencing contraceptive use among women of reproductive age were significantly associated with age (p-value=0.000), education (p-value=0.000), occupation (p-value=0.000), and residence (p-value = 0.000).Conclusion: All studied factors showed a significant association with contraceptive choice among women of reproductive age in Indonesia. Enhancing accessible and educational family planning services, particularly for low-income, rural, and adolescent populations, is essential to increase awareness and promote reproductive health.